Aberrant expression of miRNA profiles in high-fat and high-sucrose fed rats. (October 2019) - Yerlikaya, Fatma Hümeyra; Öz, Mehmet
Summary: High-fat and high-sucrose intakes were shown to contribute to syndromes such as hyperlipidemia, glucose intolerance, hypertension, and atherosclerosis. The pathogenesis of such diseases caused by high-fat and/or high-sucrose diet is unclear. The aim of the present study was to investigate plasma microRNA expression profiling in high-fat and high-sucrose fed rats. In total, 28 adult Wistar albino postnatal (8–12 weeks) male rats were involved in this experiment. The experimental animals were randomly divided four groups and fed with either standard rat chow, high-fat diet, high-sucrose diet and high-fat & high-sucrose diet for a period of 4 weeks. miRNAs were extracted from plasma and detected to miRNA expression profiling (Eighty four miRNAs) by quantitative real-time PCR (qRT-PCR) with the Fluidigm integrated microfluidic circuit technolog. Among miRNAs, expression profiles of twenty miRNAs were found to be significantly different (P < 0, 05) between groups. Of these twenty miRNAs, 1 were upregulated and 19 were downregulated with high-fat and high-sucrose feeding. The following miRNAs were downregulated: miR-130a-3p, miR-320-3p, miR-17-5p, miR-16-5p, miR-144-3p, miR-93-5p, miR-192-5p, miR-532-5p, miR-106b-5p, miR-26b-5p, miR-208b-3p, miR-23a-3p, miR-25-3p, miR-15b-5p, miR-195-5p, miR-103-3p, miR-122-5p, miR-29b-3p and miR-30a-3p and the following miRNAs were upregulated: miR-375-5p. These results indicate that aberrant expression of miRNA profiles may be associated with the development of hyperlipidemia, insulin resistance and cancer in the high-fat & high-sucrose-fed rat.